Pulse shape neutrons and gamma quanta discrimination by means of plastic scintillator of the new generation - Zhmurin, P.N.; Lebedev, V.N.; Adadurov, A.F.; Pereymak, V.N.; Gurkalenko, Yu.A. (Functional Materials, 2013)
Plastic scintillator (PS) of the new generation was developed for the pulse shape neutron and γ -quanta discrimination (n/γ -discrimination). To impart n/γ discrimination property two activation centers with different decay times were inserted in the PS. One of them transforms singlet excitation into fluorescent light, while the other – makes the same for triplet excitations. 1,4-Dimethyl-9,10-diphenylanthracene and tris(benzoylmethide) (1,10-phenantroline) Europium III – were used as activators. The figure of merit is 1.48 for this scintillator which is sufficient for reliable n/γ -discrimination.